Partisipasi Masyarakat pada Kegiatan Lomba Mewarnai dan Balap Karung di Kelurahan Pohe - Abdi Gunawan Djafar; Rahmayanti Rahmayanti; Sri Janiansi Gaib; Syafrudin Karim (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The Pantai Indah Pohe tourist area in Pohe Village, Gorontalo City, holds significant potential as a premier coastal tourism destination. However, challenges such as a lack of adequate location markers and insufficient visual promotion strategies hinder its development. To address these issues, a community service initiative was carried out by the D4 Architecture and Building Construction (ABG) Program at Gorontalo State University. The initiative aimed to enhance the visual image of the area and foster greater community involvement in promoting local tourism. The project adopted a participatory approach, actively engaging the village government, tourism awareness groups, and residents of various age groups. The activities involved creating and installing a new signage system for the